AWS for solutions architects : build and migrate your workload to Amazon Web Services using the cloud-native approach /: build and migrate your workload to Amazon Web Services using the cloud-native approach. (2023) - Shrivastava, Saurabh Kumar; Srivastav, Neelanjali; Artasanchez, Alberto
No abstract available